Dividend announcements reconsidered: Dividend changes versus dividend surprises - Christian Andres; André Betzer; Inga van den Bongard; Christian Haesner; Erik Theissen (University of Cologne, Centre for Financial Research (CFR), 2012)
This paper reconsiders the issue of share price reactions to dividend announcements. Previous papers rely almost exclusively on a naive dividend model in which the dividend change is used as a proxy for the dividend surprise. We use the difference between the actual dividend and the analyst consensus forecast as obtained from I/B/E/S as a proxy for the dividend surprise. Using data from Germany, we find significant share price reactions after dividend announcements. Once we control for analysts' expectations, the dividend change loses explanatory power. Our results thus suggest that the naive model should be abandoned. We use panel methods to analyze the determinants of the share price reactions and find evidence in favor of the cash flow signaling hypothesis and dividend clientele effects. We further find that the price reaction to dividend surprises is related to the ownership structure of the firm. The results do not support the free cash flow hypothesis.
Keywords: G35; G34; 330; Dividend Announcements; Market Efficiency; Ownership Structure; Agency Theory; Dividende; Ankündigungseffekt; Signalling; Börsenkurs; Schätzung; Deutschland